Sources of capital and debt structure in small firms - Chenchuramaiah T. Bathala; Oswald D. Bowlin; William P. Dukes (The Journal of Entrepreneurial Finance and Business Ventures, 2004)
In this paper we examine the relationship between ownership differences and small firms' financial policies using a survey of U.S. companies. The study finds that financial policies differ according to the type of ownership (private versus public) and by the ownership differences (family-owned, closely-held, or widely-held) within the private firms. The differences are in the ownership concentration, relative importance of various sources of capital, debt characteristics (sources of debt financing, debt maturity, and debt cost). A multiple regression equation estimated in the paper provides evidence relating to cross-sectional variations in debt ratios of small firms. The paper offers information asymmetry, illiquidity, and agency cost explanations for the observed differences in ownership and financial policies of small firms.
Keywords: 650